The VTI1A-TCF4 colon cancer fusion protein is a dominant negative regulator of Wnt signaling and is transcriptionally regulated by intestinal homeodomain factor CDX2. - Johanne Davidsen; Sylvester Larsen; Mehmet Coskun; Ismail Gögenur; Katja Dahlgaard; Eric Paul Bennett; Jesper Thorvald Troelsen (PLoS ONE)
Sequencing of primary colorectal tumors has identified a gene fusion in approximately 3% of colorectal cancer patients of the VTI1A and TCF7L2 genes, encoding a VTI1A-TCF4 fusion protein containing a truncated TCF4. As dysregulation of the Wnt signaling pathway is associated with colorectal cancer development and progression, the functional properties and transcriptional regulation of the VTI1A-TCF4 fusion protein may also play a role in these processes. Functional characteristics of the VTI1A-TCF4 fusion protein in Wnt signaling were analyzed in NCI-H508 and LS174T colon cancer cell lines. The NCI-H508 cell line, containing the VTI1A-TCF7L2 fusion gene, showed no active Wnt signaling, and overexpression of the VTI1A-TCF4 fusion protein in LS174T cells along with a Wnt signaling luciferase reporter plasmid showed inhibition of activity. The transcriptional regulation of the VTI1A-TCF4 fusion gene was investigated in LS174T cells where the activity of the VTI1A promoter was compared to that of the TCF7L2 promoter, and the transcription factor CDX2 was analyzed for gene regulatory activity of the VTI1A promoter through luciferase reporter gene assay using colon cancer cell lines as a model. Transfection of LS174T cells showed that the VTI1A promoter is highly active compared to the TCF7L2 promoter, and that CDX2 activates transcription of VTI1A. These results suggest that the VTI1A-TCF4 fusion protein is a dominant negative regulator of the Wnt signaling pathway, and that transcription of VTI1A is activated by CDX2.